PERBANDINGAN TINGKAT KEBAHAGIAAN ANTARA PENDUDUK DUSUN NGAJARAN, SIDOMULYO, BAMBANGLIPURO, BANTUL, DIY DENGAN PEGAWAI KEMENTERIAN KEUANGAN JAKARTA - , Mursyidi Prihantono ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aimed to compare level of happiness between Ngajaran villagers, Sidomulyo, Bambanglipuro, Bantul, DIY with employees of the Ministry of Finance (Directorate General of Budget), Jakarta. The two groups were compared to know on average, which one of the group have higher level than other. The level of happiness measured by using most of indicators and variables of Gross National Happiness (GNH) which aspects: Life Satisfaction, Positive Emotions, Negative Emotions, Spirituality, Living Standard, and Good Government. The GNH indicators were combined with happiness indicators proposed by Ibn Abbas: Qolbun Syakirun, and al-Malul Halal. The questionnaire consists of 6 indicators and 18 variables (questions) using a Likert scale. All of the questionnaires distributed, classified in to groups that fall into the 3 category: Unhappy/Not-yet Happy, Happy, and Deeply Happy. The result, for Ngajaran villagers,12 percent of respondents are Unhappy/Not-yet Happy, 86 percent Happy, and 2 percent Deeply Happy. Beside, the employees of the Ministry of Finance, 11 percent of respondents are Unhappy/Not-yet Happy, 86 percent Happy, and 3 percent Deeply Happy. From the statistical calculation known that the average level of happiness of employees of the Ministry of Finance, Jakarta, is not different with the level of happiness of the Ngajaran villagers. The most important indicator to influence level of happiness is Spirituality (both of them). For each group, the most influential indicator is Negative Emotions.